The experiences of couples in relationships characterized by alcohol dependency - Mgilane, Nomgcobo Eunice (Rhodes University, Faculty of Humanities, Department of Social Work, 2001)
The study focused on the expenences of Xhosa-speaking couples in relationships characterized by alcohol dependency. The goal was to generate greater understanding of the descriptions of relationship issues faced by alcohol dependent respondents and their partners. Specifically, the study focused on exploring how the alcohol dependent respondents relate to their partners, their behaviour at home when drinking prior to their admission for rehabilitation, the experiences of their partners in living with alcohol dependent partners and how they coped with the situation. In order to meet this goal, literature and empirical studies were conducted. The literature study focuses on the alcohol dependent individual's behaviour, his emotions, relapse, the family's coping strategies, alcohol and marital problems and the role of the social worker as part of the rehabilitation team. During the empirical research phase, a non-probability purposive sampling procedure was adopted. Fifteen alcohol dependent clients who were admitted for treatment and rehabilitation at Thembelitsha Rehabilitation Centre (TRC) were selected. These clients were admitted to TRC during the period starting from January 1997 to June 1999 and were discharged to their homes during the research study. To collect data, interviews were conducted separately to a total of thirty respondents. Two interview schedules were used, one for the alcohol dependent respondents (Appendix A) and the other for their partners (Appendix B). This study revealed a remarkable consistency in the descriptions of relationship issues faced by alcohol dependent respondents and their partners. These are abusive behaviours by alcohol dependent respondents. The partners were reluctant and feared challenging the behaviour. The way in which partners responded to drinking and the reactions of alcohol dependent respondents are indicative of the difficult issues faced by the couples. The study also revealed that couples experience communication, financial and sexual relationship problems. The study concludes with recommendations based on the research findings
Keywords: Alcoholism -- South Africa; Alcoholics -- Family relationships; Alcoholics' spouses -- South Africa; Alcoholics -- South Africa -- Conduct of life